2011
DOI: 10.1029/2011jc007105
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of net surface shortwave radiation over the tropical Indian Ocean using geostationary satellite observations: Algorithm and validation

Abstract: This paper presents the development of a methodology to estimate the net surface shortwave radiation (SWR) over tropical oceans using half‐hourly geostationary satellite estimates of outgoing longwave radiation (OLR). The collocated data set of SWR measured at 13 buoy locations over the Indian Ocean and a Meteosat‐derived OLR for the period of 2002–2009 have been used to derive an empirical relationship. The information from the solar zenith angle that determines the amount of solar radiation received at a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…We also compared the Q S and Q L from CM, CORE-II and TropFlux over the north Indian Ocean. Shahi et al [99] showed the evaluation of net shortwave radiation over the north Indian Ocean. This product was generated using buoy and satellite-derived outgoing longwave radiation data with an empirical relationship.…”
Section: Indian Oceanmentioning
confidence: 99%
“…We also compared the Q S and Q L from CM, CORE-II and TropFlux over the north Indian Ocean. Shahi et al [99] showed the evaluation of net shortwave radiation over the north Indian Ocean. This product was generated using buoy and satellite-derived outgoing longwave radiation data with an empirical relationship.…”
Section: Indian Oceanmentioning
confidence: 99%
“…Shortwave radiation measurements from satellites are quite useful where there is accurate information about clouds, permitting estimates of radiative forcing (Shahi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%